Teaching Introduction to Law: reflections and experience towards sustainable curriculum for laws foundation/ A-Level program - Ali, Adibah; Termizi, Mazbah; Azizan, Puteri Amelia Nurhananie; Panot, Serysyah Zamila; Bakri, Siti Humaiyah (2022)
This paper will highlight on the subject of Introduction to Law as one of the compulsory subjects for law students which has been taught for many years. The content of this subject is important as it is tailored to suit the need of law students. The experience of teachers who have been teaching the subject to law and non-laws students and the qualitative data of the said experiences would be gathered to improvise the subject in the near future, especially with regards to its content, as well as gauging the relevancy of the subject to be offered to non-laws students and higher level students (undergraduate). The findings should be concluded to see the perception of the teachers towards the significant contribution of the subject to the students as a whole, as well as how relevant the subject is to be sustained for future teaching and learning.